# Aptitude - Numbers - Discussion

Discussion Forum : Numbers - General Questions (Q.No. 35)
35.
 (963 + 476)2 + (963 - 476)2 = ? (963 x 963 + 476 x 476)
1449
497
2
4
None of these
Explanation:
 Given Exp. = (a + b)2 + (a - b)2 = 2(a2 + b2) = 2 (a2 + b2) (a2 + b2)
Discussion:
11 comments Page 1 of 2.

Abirami Balu said:   6 months ago
(a+b)^2+(a-b)^2
___________________
(a^2 +b^2)
= (a^2 + b^2 + 2ab)(a^2 +b^2 - 2ab)
--------------------------------------
(a^2 + b^2)
{ 2ab And - 2ab } cancels.

Then,
( a^2 + b^2) + (A^2 + b^2) becomes.
2( a^2 + b^2)
_______________
(a^2 + b ^2).

Tashi Tshering said:   3 years ago
(a+b)^2 +(a-b)^2.

Since power is 2 is even no. Even though there is -b, it will become positive.
So a^2+b^2+a^2+b^2= 2a^2+2b^2.
Take common one out 2(a^2+b^2)/(a^2+b^2).
Which is exactly divisible by the denominator.

Bruce said:   8 years ago
(a + b) ^2 + (a - b) ^2 = 2 (a^2 + b^2).
(a^2 + b^2) = 1/2 [(a + b) ^2 + (a - b) ^2].

Then,
2 (a^2 + b^2) ÷ 1/2[(a + b) ^2 + (a - b) ^2].

Then, 2 * 2/1 = 4.

Ananthu said:   3 years ago
(a+b) ^2+ (a-b) ^2/ (a^2 + b^2) = a^2+b^2+2ab+a^2+b^2-2ab/(a^2 + b^2).

2a^2+2b^2/ (a^2 + b^2) = 2 (a^2+b^2)/(a^2 + b^2) = 2.
(1)

Abhishek guruji said:   8 years ago
(a+b)^2 + (a-b)^2,

a^2 + b^2 + 2ab + a^2 + b^2 - 2ab,

a^2 + b^2 + a^2 + b^2,

2a^2 + 2b^2,

2(a^2+b^2).

Please explain the problem, I could not understand it.

Kamlesh bisht said:   5 years ago
a^2+b^2 = 1/2(a+b)^2+(a+b)^2 use this formula.
(1)

Swechha said:   6 years ago